The Chilean Health System: 20 Years of Reforms El sistema de salud chileno: 20 años de reformas - Annick Manuel (Instituto Nacional de Salud Pública, 2002)
The Chilean health care system has been intensively reformed in the past 20 years. Reforms under the Pinochet government (1973-1990) aimed mainly at the decentralization of the system and the development of a private sector. Decentralization involved both a deconcentration process and the devolution of primary health care to municipalities. The democratic governments after 1990 chose to preserve the core organization but introduced reforms intended to correct the system's failures and to increase both efficiency and equity. The present article briefly explains the current organization of the Chilean health care system. It also reviews the different reforms introduced in the past 20 years, from the Pinochet regime to the democratic governments. Finally, a brief discussion describes the strengths and weaknesses of the system, as well as the challenges it currently faces. El sistema de salud chileno ha sido intensamente reformado en los últimos 20 años. Las reformas bajo el gobierno de Pinochet (1973-1990) apuntaron principalmente a la descentralización del sistema y al desarrollo del sector privado. La descentralización involucró un proceso de desconcentración y la devolución de las unidades de atención primaria a las municipalidades. Los gobiernos democráticos posteriores a 1990 escogieron preservar el núcleo organizacional, pero las reformas introducidas buscaron corregir las fallas del sistema y aumentar la eficacia y la equidad. El presente artículo explica brevemente la organización actual del sistema de salud chileno y revisa las diferentes reformas introducidas en los últimos 20 años desde el régimen de Pinochet hasta los gobiernos democráticos. Finalmente, presenta una discusión breve para describir las fortalezas y debilidades del sistema, así como los desafíos que enfrenta actualmente.